Revision of the Agrilus purpurifrons species-group (Coleoptera, Buprestidae, Agrilinae) - Jendek, Eduard; Nakládal, Oto (Zootaxa, 2019)
The Agrilus purpurifrons species-group comprising twelve species from the Oriental region is defined and revised. A key to species is provided and complemented with illustrations of habitus and genitalia. Three new species are described: Agrilus cameronius sp. nov. (Malaysia); A. puncak sp. nov. (Indonesia); and A. vendibilis sp. nov. (Indonesia). The following taxonomic changes are proposed: the specific names lacroixi Obenberger, 1936 syn. nov. and chapaensis Descarpentries & Villiers, 1967 syn. nov. are junior synonyms in the synonymy of A. morio Kerremans, 1895; the name rousselatae Baudon, 1968 stat. rev. is removed from the synonymy of A. lacroixi Obenberger, 1936 and revalidated as the specific name of A. rousselatae Baudon, 1968.